Examining the open-source datasets for water quantity and quality using the soil and water assessment tool (SWAT) - İsmail Bilal Peker; Sezar Gülbaz (Water Science and Technology, 2023)
Water quality modeling is very important for the management of water resources. In this study, the upper part of the Porsuk Basin in Türkiye is analyzed using SWAT. In the analysis, in addition to the data provided by the General Directorate of State Hydraulic Works (DSI), the freely available flow and water quality data from the GEMStat data portal were used. This study presents a discussion of the practicality of GEMStat data for a water quality model. For this purpose, firstly, the SWAT model was constructed with freely available global data sources on elevation, land use/land cover, and soil type. Then, the model flow outputs were calibrated and validated for both DSI and GEMStat data in three different time periods. As a result, the flow calibration and validation success in the daily time step is 0.64 and 0.44 according to the Nash–Sutcliffe efficiency (NSE). The model was also validated using GEMStat flow data and calibrated using GEMStat water quality data such as nitrate (NO3), total suspended solids (TSS), and dissolved oxygen (DO) with a reasonable value. Hence, the results showed that GEMStat flow and water quality data can be used as auxiliary open-source data in the modeling process. HIGHLIGHTS The importance of data monitoring and the benefit of the freely available data were emphasized.; The usability of the data obtained from the global data provider portal GEMStat was tested using SWAT.; Model-generated flow and water quality data showed reasonable fit (NSE values between 0.35 and 0.64) with the real data in the daily time step.;